2011
DOI: 10.1007/s00248-011-9851-6
|View full text |Cite
|
Sign up to set email alerts
|

Host Associations Between Fungal Root Endophytes and Boreal Trees

Abstract: Fungal root endophytes colonize root tissue concomitantly with mycorrhizal fungi, but their identities and host preferences are largely unknown. We cultured fungal endophytes from surface-sterilized Cenococcum geophilum ectomycorrhizae of Betula papyrifera, Abies balsamea, and Picea glauca from two boreal sites in eastern Canada. Isolates were initially grouped on the basis of cultural morphology and then identified by internal transcribed spacer ribosomal DNA sequencing or by PCR restriction fragment length p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 64 publications
5
45
2
1
Order By: Relevance
“…Recent evidence also indicates that some fungal root endophytes exhibit preference for particular host plants (Gr€ unig et al, 2008;Tedersoo et al, 2009;Kernaghan and Patriquin, 2011;Quilliam and Jones, 2012;Tejesvi et al, 2013), although examples of specificity at levels seen in some ECM fungi are lacking (Molina et al, 1992;Toju et al, 2013a). There is also increasing evidence that some fungal root endophytes prefer ECM formed by particular species of ectomycorrhizal fungi (Urban et al, 2008;Tedersoo et al, 2009;Izumi and Finlay, 2011;Yamamoto et al, 2014), potentially representing a second level of root endophyte selection.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recent evidence also indicates that some fungal root endophytes exhibit preference for particular host plants (Gr€ unig et al, 2008;Tedersoo et al, 2009;Kernaghan and Patriquin, 2011;Quilliam and Jones, 2012;Tejesvi et al, 2013), although examples of specificity at levels seen in some ECM fungi are lacking (Molina et al, 1992;Toju et al, 2013a). There is also increasing evidence that some fungal root endophytes prefer ECM formed by particular species of ectomycorrhizal fungi (Urban et al, 2008;Tedersoo et al, 2009;Izumi and Finlay, 2011;Yamamoto et al, 2014), potentially representing a second level of root endophyte selection.…”
Section: Introductionmentioning
confidence: 92%
“…Although DSE are common, woody roots and ECM are colonized by a much more diverse array of fungi, including many non-melanized species, as demonstrated by several culture dependent (Schild et al, 1988;Fisher et al, 1991;Girlanda and Luppi-Mosca, 1995;Girlanda et al, 2002;Hoff et al, 2004;Summerbell, 2005;Kernaghan and Patriquin, 2011), and culture independent studies (Kernaghan et al, 2003;Kwa sna et al, 2008;Urban et al, 2008;Tedersoo et al, 2009;Izumi and Finlay, 2011;Toju et al, 2013a).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Los medios de cultivo utilizados para el aislamiento son variados; por ejemplo, se ha utilizado el medio Czapek enriquecido con sacarosa, agar extracto de malta (AEM), medio de malta-levadura (MML), medio Melin-Norkrans (MMN), agar papa-dextrosa (APD), agar soya-tríptica (AST; Kernaghan et al, 2003;Kernaghan y Patriquin, 2011). En estos medios de cultivo se recomienda aplicar antibióticos (estreptomicina, ampicilina, tetraciclina, oxitetraciclina, penicilina y cloranfenicol) que eviten el crecimiento de bacterias (Yuan et al, 2010b), o bien, usar fungicidas como el benomil (Kernaghan et al, 2003;Kernaghan y Patriquin, 2011). Las muestras se incuban en oscuridad bajo un intervalo de temperatura de 20-25 °C.…”
Section: Identidad Taxonómica Y Aislamientounclassified
“…Accordingly, numerous studies have shown that host preference or recurrence is important for the formation of biotrophic [165][166][167][168], lignolytic [50], and pathogenic [169] fungal communities. Thus, the description of all microbial diversity apparently requires an assessment of all hosts and habitats.…”
Section: They Are Habitat Specialists and We Have Not Yet Evaluated mentioning
confidence: 99%